The incidence of ABO, Kell and Rh system blood groups in general population of Qazvin, Iran - Ahmadi, Mohammad Hossein; Maroufi, Faezeh; Kelki, Hoora; Zolghadri, Narges; Moradi, Fatemeh; Maali, Amirhosein; Azad, Mehdi (Archives of Advances in Biosciences, 2019)
Introduction:ABO antigens and the glycoproteins constituting the blood groups such as Kell and Rh systems are the mostly focused blood groups in transfusion medicine. Their importance is tightly associated with the presence of natural isoantibodies, their protein structure, and immunogenicity. The aim of our study was to assess the distribution of major Rh and Kell antigens and the most probable genotype in a normal population of Qazvin city, Iran.Materials and methods:This study was done on 1000 healthy people who were candidates for getting driver’s license. The blood samples were tested for Kell, ABO and major Rh antigens by standard tube agglutination method.Results:Out of 1000 samples studied, the prevalence of RhD was 86.6%. The incidence of other Rh antigens i.e. C, E, c and e was 73%, 29.8%, 72.1%, and 95.9% respectively. The most common phenotype in the samples was DCce and the least one was shown to be CcEe. Kell antigen frequency was 8.2%. On the other hand, 91.8% of people were indicated to be negative for the Kell antigen.Conclusion:Taken together, the amount of the individuals negative for the Kell and Rh system are adequate to provide new policies for identification of these antigens for both blood donors and recipients.